CONFESSIONAL MOTIVES IN THE WORKS OF THE JAPANESE WRITER SAYAKA MURATA (Academia Science Repository, 2023)
This article devoted to autobiographical motives and their features in contemporary Japanese novels using the example of Sayaka Murata's works. Each of Sayaka Murata's works is original and original in its own way, but they are all united by the acute, most common problems of our society. The problems inherent in each country and especially concerning Japanese society are touched upon.